2017
DOI: 10.1111/mec.14279
|View full text |Cite
|
Sign up to set email alerts
|

Widespread hybridization and bidirectional introgression in sympatric species of coral reef fish

Abstract: Coral reefs are highly diverse ecosystems, where numerous closely related species often coexist. How new species arise and are maintained in these high geneflow environments have been long-standing conundrums. Hybridization and patterns of introgression between sympatric species provide a unique insight into the mechanisms of speciation and the maintenance of species boundaries. In this study, we investigate the extent of hybridization between two closely related species of coral reef fish: the common coral tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 103 publications
(124 reference statements)
2
23
0
1
Order By: Relevance
“…Indeed, the relative abundance of Z. scopas, Z. flavescens, and their hybrids was estimated at 90.9%, 5.6%, and 3.5%, respectively (authors’ unpublished data recorded from 2013 to 2016, based on 102 visual transects over 32 sites, total number of Zebrasoma individuals = 428). A pattern of directional introgression, as was observed here, that may be predicted by skewed abundances of parental species, is not unusual, as was reported in several other coral reef fish species (Crow et al., ; Harrison et al., ; Montanari, Hobbs, Pratchett, Bay, & Van Herwerden, ; Yaakub, Bellwood, Herwerden, & Walsh, ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, the relative abundance of Z. scopas, Z. flavescens, and their hybrids was estimated at 90.9%, 5.6%, and 3.5%, respectively (authors’ unpublished data recorded from 2013 to 2016, based on 102 visual transects over 32 sites, total number of Zebrasoma individuals = 428). A pattern of directional introgression, as was observed here, that may be predicted by skewed abundances of parental species, is not unusual, as was reported in several other coral reef fish species (Crow et al., ; Harrison et al., ; Montanari, Hobbs, Pratchett, Bay, & Van Herwerden, ; Yaakub, Bellwood, Herwerden, & Walsh, ).…”
Section: Resultssupporting
confidence: 85%
“…However, based on outlier loci (where species are distinguishable), we did not find evidence of introgression in Z. flavescens individuals from Hawaii. We also found that Z. scopas from Moorea hardly contain any genetic material assigned to Z. flavescens (Figure 3 observed here, that may be predicted by skewed abundances of parental species, is not unusual, as was reported in several other coral reef fish species (Crow et al, 2007;Harrison et al, 2017;Montanari, Hobbs, Pratchett, Bay, & Van Herwerden, 2017;Yaakub, Bellwood, Herwerden, & Walsh, 2006).…”
Section: Introgression and Hybridizationsupporting
confidence: 81%
“…For example, hybridization between eight pairs of reef fish species in the Cocos–Christmas suture zone was first identified based on intermediate coloration and was later supported by observations of heterospecific breeding pairs, heterospecific social groups, and genetic data (DiBattista et al, ; Hobbs et al, ; Marie, Herwerden, Choat, & Hobbs, ; Montanari, Hobbs, Pratchett, Bay, & Herwerden, ; Payet et al, ; Yaakub, Bellwood, & Herwerden, ; Yaakub, Bellwood, Herwerden, & Walsh, ). In some cases, hybridization is not detected using coloration because hybridization occurred in distant past (Koblmüller, Egger, Sturmbauer, & Sefc, ; Kuriiwa, Hanzawa, Yoshino, Kimura, & Nishida, ), or hybrids are rare and/or because backcrossed individuals look like the parent species (Harrison et al, ). Thus, genetic markers are useful for revealing cryptic and historical cases of hybridization in our oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Suture zones are phylogenetically important as hybridization can have significant consequences to speciation processes (Abbott, Hegarty, Hiscock, & Brennan, 2010;Mallet, 2007). Hybrids may (a) be unfit and favor reproductive isolation between species (Via, 2009;Wu, 2001), (b) be fit and facilitate recurring introgression and reverse speciation (Harrison et al, 2017;Kleindorfer et al, 2014), or (c) even generate new species and radiation events (Mallet, 2007;Seehausen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these cases suggest that incomplete postzygotic barriers may still have impact on the fitness of hybrid offspring, and this process may be responsible for the maintenance of species boundaries despite frequent hybridization in the HMR. Sufficient fertile F 1 hybrids can produce backcrosses and act as potential genetic bridge between both parental species for introgression (Cannon & Scher, 2017;Harrison et al, 2017;Twyford, Kidner, & Ennos, 2015;Yatabe, Kane, Scotti-Saintagne, & Rieseberg, 2007). Hence, frequent backcrossing may lead to introgression of genetic material to one or both parents.…”
Section: The Effect Of Reproductive Barriers On Hybrid Zonesmentioning
confidence: 99%